Development of Smart Blind Stick using Global Positioning System - Yamuna Mahadevan; Hairol Anuar, Siti Haryanti (MASE - Media Applied and Engineering, 2024)
The smart blind stick using Global Positioning System (GPS) is an assistive device designed to enhance the mobility and independence of visually impaired individuals. Traditional blind sticks provide basic obstacle detection and aid in navigation, but it lacks an advanced feature for precise location tracking and route guidance. This project aims to leverage GPS technology by developing a prototype of smart blind stick that can send information to the user's position and provide audio-based for alert. The proposed system incorporates a GPS module to acquire real-time coordinates and a microcontroller to process the data. The device is designed to be lightweight, portable, and user-friendly. The software component involves developing a user interface that allows the user to input their destination or select pre-defined routes. The system then calculates the optimal path based on the GPS coordinates and provides step-by-step directions, that include distance and directional cues. To enhance the functionality, additional features of obstacle detection using ultrasonic sensors have been integrated. These sensors can alert the user about potential obstacles in them path, further improving safety during navigation. The smart blind stick using GPS aims to offer a cost-effective and efficient solution for visually impaired individuals, enabling them to navigate unfamiliar environments with confidence. The success of this project will be evaluated through simple user testing and feedback collection.